1996
DOI: 10.1097/00000542-199612000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin Flora as a Potential Source of Epidural Abscess

Abstract: In a large proportion of patients, isolation of viable organisms from excised skin specimens after disinfection with 10% PVP-I suggests that contamination of the epidural space by the skin flora may be a potential mechanism of epidural infection associated with epidural block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(32 citation statements)
references
References 15 publications
2
27
0
3
Order By: Relevance
“…Finally, Sato and colleagues 14 have also shown that resident bacteria are hidden deep in hair follicles and orifices of sebaceous glands, locations that are often protected from disinfectants by lipids overlying the stratum corneum. Therefore, despite meticulous attention to skin disinfection, microorganisms may still persist under the skin when using antiseptics that are unable to penetrate the stratum corneum.…”
Section: Sources Of Injectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, Sato and colleagues 14 have also shown that resident bacteria are hidden deep in hair follicles and orifices of sebaceous glands, locations that are often protected from disinfectants by lipids overlying the stratum corneum. Therefore, despite meticulous attention to skin disinfection, microorganisms may still persist under the skin when using antiseptics that are unable to penetrate the stratum corneum.…”
Section: Sources Of Injectionmentioning
confidence: 99%
“…Extrinsic sources of infection include invasion of skin bacteria through a needle tract, [14][15][16][17][18] contaminated syringes, 19 catheter hubs, 20 local anesthetics, 21 or breaches in aseptic technique. [21][22][23][24] The migration of skin bacteria through needle puncture sites is considered to be a major source of epidural colonization.…”
Section: Sources Of Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catheters kept in place for a short time are generally colonized by skin flora present on the catheter insertion sites during catheter placement [4]. Thus, effective cutaneous antisepsis before epidural insertion may reduce catheter colonization and epidural-catheter-related serious infection.…”
Section: Background and Purposesmentioning
confidence: 99%